1985
DOI: 10.1002/oms.1210201212
|View full text |Cite
|
Sign up to set email alerts
|

Stereoisomeric effects on mass spectral fragmentations of chloronorbornanones

Abstract: Stereoelectronic factors allow facile CI' atom loss from the ero-6-chloro-2-norbornanone radical cation but not from the endo-6-epimer. The predominant primary reaction in the endo-6 and in the m o d and endo-5 compounds is HCI elimination. While C1' e l i n a t i o n occurs with skeletal reorganization, HCI loss, at least in part, does not. The 5-chloro isomers undergo a regiospecific McLafferty rearrangement which occurs relatively slowly in competition with CI' and HCI loss. The use of energy-resolved forms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1987
1987
2009
2009

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 25 publications
(1 reference statement)
0
1
0
Order By: Relevance
“…In the rigid 2-norbornanone series, two/~ isomers, ezo-6 and anti-7, have a geometry in which the stereoelectronics approximates the ideal 90/180 conformation, and thus exhibit comparable LITMO mixing. A LITMO plot for ezo-6 is shown in Figure 5 where been synthesized [56] and its absorption spectrum , -max{~M*On 299 am (e = 68)) and reduction potential (-1.44 V. ~ersus SCE) [58] attest to the anticipated lowering of the LUMO energy. Electron transmission spectroscopy (ETS) is another excellent probe for LUMO perturbation [57,58] and the results of an ET$ study of ezo-6 (relative to ¢zo-5 and monofunctional reference compounds) are shown in Figure 6.…”
Section: O Photochemical Studiesmentioning
confidence: 98%
“…In the rigid 2-norbornanone series, two/~ isomers, ezo-6 and anti-7, have a geometry in which the stereoelectronics approximates the ideal 90/180 conformation, and thus exhibit comparable LITMO mixing. A LITMO plot for ezo-6 is shown in Figure 5 where been synthesized [56] and its absorption spectrum , -max{~M*On 299 am (e = 68)) and reduction potential (-1.44 V. ~ersus SCE) [58] attest to the anticipated lowering of the LUMO energy. Electron transmission spectroscopy (ETS) is another excellent probe for LUMO perturbation [57,58] and the results of an ET$ study of ezo-6 (relative to ¢zo-5 and monofunctional reference compounds) are shown in Figure 6.…”
Section: O Photochemical Studiesmentioning
confidence: 98%